2019
DOI: 10.3390/electronics8040419
|View full text |Cite
|
Sign up to set email alerts
|

Robust Stable Control Design for AC Power Supply Applications

Abstract: This paper applies modified feedback technology to carry out the exact steady-state and fast transient in a high-performance alternating current (AC) power supply. The presented scheme displays the virtues of a finite-time convergence control (FTCC) and a discrete grey prediction model (DGPM). The FTCC, derived from a terminal sliding-mode (TSM) design principle, can produce the finite system-state convergence time and evade the singularity. It is noteworthy that the chattering/steady-state error around the FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Chang et al reported on "Robust Stable Control Design for AC Power Supply Applications" [1] and proposed an improved feedback algorithm by binary particle swarm optimization (BPSO)-based nonsingular terminal sliding mode control (NTSMC) for DC-AC converters. The NTSMC can create limited system state convergence time and allow singularity avoidance.…”
Section: The Topic Of Electronics and Its Applicationsmentioning
confidence: 99%
“…Chang et al reported on "Robust Stable Control Design for AC Power Supply Applications" [1] and proposed an improved feedback algorithm by binary particle swarm optimization (BPSO)-based nonsingular terminal sliding mode control (NTSMC) for DC-AC converters. The NTSMC can create limited system state convergence time and allow singularity avoidance.…”
Section: The Topic Of Electronics and Its Applicationsmentioning
confidence: 99%